2015
DOI: 10.5194/gmdd-8-5983-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adjoint of the Global Eulerian–Lagrangian Coupled Atmospheric transport model (A-GELCA v1.0): development and validation

Abstract: We present the development of the Adjoint of the Global Eulerian-Lagrangian Coupled Atmospheric (A-GELCA) model that consists of the National Institute for Environmental Studies (NIES) model as an Eulerian threedimensional transport model (TM), and FLEXPART (FLEXible PARTicle dispersion model) as the Lagrangian Particle Dispersion Model (LPDM). The forward tangent linear and adjoint components of the Eulerian model were constructed directly from the original NIES TM code using an automatic differentiation tool… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Although GEOS-Chem was originally developed as a global CTM [49], several versions of its nested model have become available in recent years [31,50,51], allowing GEOS-Chem to be applied as a regional CTM. The adjoint method, which has excellent efficiency in calculating SS in a single simulation for many sources, has been developed for several models [31,32,[52][53][54][55]. As a representative application, the GEOS-Chem adjoint was used to efficiently estimate the sensitivity of a user-defined cost function to model parameters (e.g., emission rates and reaction rates) [23].…”
Section: Ss Simulationmentioning
confidence: 99%
“…Although GEOS-Chem was originally developed as a global CTM [49], several versions of its nested model have become available in recent years [31,50,51], allowing GEOS-Chem to be applied as a regional CTM. The adjoint method, which has excellent efficiency in calculating SS in a single simulation for many sources, has been developed for several models [31,32,[52][53][54][55]. As a representative application, the GEOS-Chem adjoint was used to efficiently estimate the sensitivity of a user-defined cost function to model parameters (e.g., emission rates and reaction rates) [23].…”
Section: Ss Simulationmentioning
confidence: 99%
“…The potential for further improvement includes moving from gross annual averaging to more accurate seasonal or monthly averaging. In addition, it is possible to study the sensitivity of XCO 2 observations using the adjoint of the global Eulerian-Lagrangian coupled atmospheric transport model (Belikov et al, 2016), which can resolve long-term, synoptic and hourly variation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…(2013b) reported that the NIES model is able to successfully reproduce the vertical profile of CO 2 as well as the seasonal and interannual variability in XCO 2 . A comparison of modelled output with TCCON observations (Belikov et al, 2013b) revealed model biases of ±0.2 % for XCO 2 ; on this basis we assume that the NIES TM is able to successfully reproduce the vertical profile of CO 2 at the locations of TC-CON sites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations